2010
DOI: 10.1111/j.1479-828x.2009.01106.x
|View full text |Cite|
|
Sign up to set email alerts
|

Use of additional oxytocin to reduce blood loss at elective caesarean section: A randomised control trial

Abstract: An additional oxytocin infusion after 5 IU oxytocin bolus infusion at elective C/S may reduce blood loss and required blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…13 Additional oxytocic needed among the groups in this study is consistent with the result reported in other similar studies that women in the bolus and infusion group were less likely to require an additional uterotonic agent than those in the bolus only group. [13][14][15] In this study, post caesarean section Hb% significantly decreased within the groups after 24 hours; however, there was no significant difference in Hb% between the groups. In other study, it was shown that the difference of preoperative and postoperative Hb% of misoprostol and oxytocin groups was not remarkable which is consistent with this study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…13 Additional oxytocic needed among the groups in this study is consistent with the result reported in other similar studies that women in the bolus and infusion group were less likely to require an additional uterotonic agent than those in the bolus only group. [13][14][15] In this study, post caesarean section Hb% significantly decreased within the groups after 24 hours; however, there was no significant difference in Hb% between the groups. In other study, it was shown that the difference of preoperative and postoperative Hb% of misoprostol and oxytocin groups was not remarkable which is consistent with this study.…”
Section: Discussionmentioning
confidence: 71%
“…3 Güngördük et al showed a reduction of major obstetric haemorrhage in oxytocin bolus and 30 IU oxytocin infusion than oxytocin bolus only. 15 Conde-Agudelo et al showed that misoprostol combined with oxytocin appears to be more effective than oxytocin alone in reducing intraoperative and postoperative hemorrhage during cesarean section; however, there was no significant differences in intraoperative and postoperative hemorrhage when misoprostol was compared to oxytocin. 17 Side effects occurred in 7 (23.3%) patients of group 1, 18 (60.0%) in group 2, and 6 (20.0%) in group 3.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 Women in the higher dose group had significantly lower mean estimated blood loss and lower frequencies of blood loss greater than 500ml or greater than 1000 ml, need for uterotonic treatment or blood transfusion. 18,20 In another small study of cesareans, higher dose of oxytocin was associated with a higher uterine tone and a non-significant reduction in need for additional uterotonic. 19 Finally, in the previous trial at our institution 80 units as compared with 10 units of prophylactic oxytocin reduced the need for any uterotonic treatment as well as the need for treatment with second line agents among women who underwent cesarean delivery after labor.…”
Section: Discussionmentioning
confidence: 95%
“…11,1820 Typically, these studies have associated higher doses of prophylactic oxytocin with beneficial impact on outcomes such as estimated blood loss, decline in hematocrit or need for additional uterotonics among women who underwent cesarean delivery. 11,1820 In two studies, women undergoing scheduled cesarean received a 5 unit IV bolus versus 35 units (5 unit bolus+30 units over 4 hours) of prophylactic oxytocin. 18,20 Women in the higher dose group had significantly lower mean estimated blood loss and lower frequencies of blood loss greater than 500ml or greater than 1000 ml, need for uterotonic treatment or blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation